VARIOUS METHODS OF ALUMINUM MELTING DUST DROSS FRACTION GRANUTATION AND THE RESEARCH OF CONTINUOUS GRANULATION POSSIBILITIES - Sedo, Jan; Polakova, Silvia; Cuchtova, Daniela (European Scientific Journal, ESJ, 2015)
Dust fractions from aluminum dross treatment are environmental load for every company in this industry sector. They are classified as waste due to their physical and primarily chemical parameters and require thus higher attention. On the other hand, the same parameters classify them as a possible source of chemical materials usable in other industry sectors. Dross treatment and the following treatment of their dust non-melting fractions are also important for such waste type producers as well as for product consumers produced from this waste